2022
DOI: 10.3349/ymj.2022.63.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Basic Principles and Clinical Applications of CRISPR-Based Genome Editing

Abstract: Advances in sequencing technologies have facilitated the discovery of previously unknown genetic variants in both inherited and acquired disorders, and tools to correct these pathogenic variants are rapidly evolving. Since the first introduction of CRISPR-Cas9 in 2012, the field of CRISPR-based genome editing has progressed immensely, giving hope to many patients suffering from genetic disorders that lack effective treatment. In this review, we will examine the basic principles of CRISPR-based genome editing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 71 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…However, MYMX expression is strictly restricted to myoblast fusion ( 5 ), and studies in mice suggest that overexpression of muscle fusogens could negatively impact muscle fiber integrity in dystrophic conditions ( 42 ). Recently, CRISPR/Cas9 base editing has emerged as an attractive therapeutic genome editing tool to directly correct disease-causing mutations and maintain endogenous expression levels of the corrected genes ( 53 ). Several studies have shown that in vivo delivery of base editors by adeno-associated viruses can target specific tissues, edit target genes, restore gene function, and ameliorate a broad spectrum of pathologies, including muscular dystrophies, metabolic disorders, and hereditary blindness ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, MYMX expression is strictly restricted to myoblast fusion ( 5 ), and studies in mice suggest that overexpression of muscle fusogens could negatively impact muscle fiber integrity in dystrophic conditions ( 42 ). Recently, CRISPR/Cas9 base editing has emerged as an attractive therapeutic genome editing tool to directly correct disease-causing mutations and maintain endogenous expression levels of the corrected genes ( 53 ). Several studies have shown that in vivo delivery of base editors by adeno-associated viruses can target specific tissues, edit target genes, restore gene function, and ameliorate a broad spectrum of pathologies, including muscular dystrophies, metabolic disorders, and hereditary blindness ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CRISPR/Cas9 base editing has emerged as an attractive therapeutic genome editing tool to directly correct disease-causing mutations and maintain endogenous expression levels of the corrected genes ( 53 ). Several studies have shown that in vivo delivery of base editors by adeno-associated viruses can target specific tissues, edit target genes, restore gene function, and ameliorate a broad spectrum of pathologies, including muscular dystrophies, metabolic disorders, and hereditary blindness ( 53 ). Using patient-derived iPSC myotubes, we show that the MYMX R46* variant is amenable to therapeutic correction by base editing.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is carried out by a process called intein-mediated trans-splicing, which to some degree is similar to mRNA splicing [ 83 , 84 ]. This method has been used to deliver base and prime editing systems, which were found to be quite promising [ 85 , 86 ]. Another challenging issue for in vivo delivery is the pre-existing immunogenicity against the bacterial Cas9 protein and AAV capsid.…”
Section: Viral Vectors and Extracellular Vesicles Used In Crispr-cas9...mentioning
confidence: 99%
“…The basic model consists of three steps: acquisition, expression, and intervention. [27][28][29] The CRISPR-Cas system is divided into two categories depending on the structure and evolutionary relationship of the Cas protein. There are six types of Cas, the most common being: Cas3 (Type I), Cas9 (Type II), Cas10 (Type III), Csf1 (Type IV), Cpf1/ Cas12 (Type V), and Cas13 (Type VI).…”
Section: Crispr-cas Systemmentioning
confidence: 99%